Precision validation of MIPAS-Envisat products - Piccolo, C; Dudhia, A (2007)
This paper discusses the variation and validation of the precision, or estimated random error, associated with the ESA Level 2 products from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS). This quantity represents the propagation of the radiometric noise from the spectra through the retrieval process into the Level 2 profile values. The noise itself varies with time, steadily rising between ice decontamination events, but the Level 2 precision has a greater variation due to the atmospheric temperature which controls the total radiance received. Hence, for all species, the precision varies latitudinally/seasonally with temperature, with a small superimposed temporal structure determined by the degree of ice contamination on the detectors. The precision validation involves comparing two MIPAS retrievals at the intersections of ascending/descending orbits. For 5 days per month of full resolution MIPAS operation, the standard deviation of the matching profile pairs is computed and compared with the precision given in the MIPAS Level 2 data, except for NO2 since it has a large diurnal variation between ascending/descending intersections. Even taking into account the propagation of the pressure-temperature retrieval errors into the VMR retrieval, the standard deviation of the matching pairs is usually a factor 1-2 larger than the precision. This is thought to be due to effects such as horizontal inhomogeneity of the atmosphere and instability of the retrieval.